EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DAN THREE STEPS INTERVIEW (TSI) PADA MATERI FUNGSI DITINJAU DARI KECERDASAN LOGIS MATEMATIS - Purnamasari, Anita; Mardiyana, Mardiyana; Subanti, Sri (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The purpose of this study was to determine the effect of the learning models TAI, PC, and direct learning model on mathematics learning achievement viewed from the students adversity quotient. The type of this study was quasi experimental study with 3x3 factorial design. The population were the eighth-grade students of junior high schools in Sukoharjo Regency in the academic year of 2015/2016. Instruments used for data collection were mathematics achievement test and adversity quotient questionnaire. The data analysis technique used was the two-way ANAVA with unbalanced cell. Based on the hipothesis test, it was concluded as follows. 1) The mathematics learning achie vement of TAI was better than PC and direct learning model, the mathematics learning achievement of PC was better than direct learning model. 2) The mathematics learning achievement of students with climbers category were better than campers and quitters category. Students with campers category were better than quitters category. 3) Students with climbers category who were treated by TAI, PC, and direct learning models had same mathematics learning achievement; students with campers category who were treated by TAI was same of PC and was better than direct learning model, PC was better than direct learning model; students with quitters category who were treated by TAI had same mathematics learning achievement with PC and direct learning model, PC was better than direct learning model. 4) In TAI learning model, the mathematics learning achievement of climbers category were better than campers and quitters category, the mathematics learning achievement of campers category was better than quitters category; in PC learning model, students with climbers category has equal of campers and was better than quitters category, the mathematics learning achievement of campers category were better than quitters category; in direct learning model, students with climbers category has better mathematics learning achievement than campers and quitters category, students with campers category has equal of quitters category.Keywords: Team Assisted Individualization, Pairs Check, Direct Learning Model, Adversity Quotient, Achievement.